Deposição de filmes finos de SnO2 e GaAs, visando confecção de dispositivos baseados na heterojunção SnO2/GaAs - Bueno, Cristina de Freitas [UNESP] (2015)
The purpose of this work is the deposition of GaAs thin films through the simple resistive evaporation technique, and SnO2 thin films doped with Eu3+ rare-earth ion, by sol-gel-dip-coating process, combining a semiconductor material with high electron mobility and direct transition (GaAs), with a wide bandgap semiconductor (SnO2), and natural n-type conductivity, where the rare-earth ion emission, including Eu3+, is very efficient. Samples of these two materials are investigated separately, where SnO2:Eu3+ are in the form of thin films or pressed powder into pellets, as well a combined heterostructure. Thus, results for GaAs, SnO2:2%Eu thin films, Eu-doped SnO2 xerogels, and thin films forming the heterostructure GaAs/SnO2:2%Eu are shown and discussed in the this paper. X-ray difraction (XRD) measurements have shown the main crystallographic directios of SnO2 crystals, with identified rutile structure and cassiterite phase, where the estimated crystallite size along the (101) plane has yielded the values 16nm and 19nm, for film deposited on glass and quartz substrates, respectively. Scanning electron microscopy (SEM) images show the surface of heterojunction GaAs/SnO2:2%Eu, presenting an inhomogeneous character with lighter regions, where the energy-dispersive X-ray spectroscopic (EDX) analysis allows obtaining a range of up to 700% variation in the Sn/Eu relative composition in these regions. Protolominescence (PL) measurements enabled the observation of Eu3+ lines, manly to the case of heterostructure samples, and the appearance of a broad band, which shifts to higher energy according to the thermal annealing temperature. Electrical characterization enabled the evaluation of the temperature effect as well saturation by a monochromatic ligh source. Then, it is expected that the study of luminescent mechanisms and electrical behavior help in the production of new devices, such as electroluminescent devices, combining the properties of...